Arithmetic version of boolean algebra - Azram, Mohammad; Daoud, Jamal Ibrahim; Elfaki, Faiz Ahmed Mohamed (2010)
In this paper, we discuss that the logical results in Boolean algebra can equally be derived with ordinary algebraic operations. We establish arithmetic versions of the common logical propositions inclusive of Sheffer stroke (Nand connective) and Peirce’s arrow (Nor connective) which are very important to design circuit diagrams. We present the comparison of some basic logical Boolean expressions and their arithmetic version through the truth tables. Finally, we establish the fundamental logical equivalent proposition via arithmetic versions.